FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MENURUT TEORI SIGNALLING (Studi Pada Perusahaan Manufaktur SektorlIndustri Barang Konsumsi yang Terdaftarxdi Bursa EfekiIndonesia (BEI) Tahun 2017–2020) - Agung Santosa, R Ery Wibowo (Jurnal Akuntansi dan Bisnis, 2022)
This study aims to analyze1the effect of firm size, earnings quality, and investment decisions on firmavalue. The populationnin thisbstudy theaIndustrial SectorzManufacturing companieszlisted on the1Indonesia StockbExchange (IDX) inh2017–2020. The sampling methodtin this studyouses a purposive sampling technique, with a research samplelof 31 companies. The analytical method used is the SPSS 25bprogram. Data analysisnuses multipleylinearoregression. The resultsishowed that the coefficientlof determinationaresulted inbthe AdjustedxR2 41,6%. Basedlon the results oflthe simultaneous significancebtest showxthat the variable of firm size, earningsqquality and investment decisions simultaneouslyohave a positiveveffect on firmbvalue. The partial significance testzshows that firmisize has nozeffect on firmavalue, earningskquality has a negativeleffect on firmrvalue, and linvestment decisionsnhave a positiveceffect on firmovalue.Keywords : Firm size, earnings quality, investment decisions, firmovalue.